Ketakutan terhadap COVID-19 dengan Kecemasan Karier di Masa Depan pada Mahasiswa Tingkat Akhir - Fathia Nurul Amrina; Talitha Lintang Pertiwi (Philanthropy: Journal of Psychology)
Abstract. The condition of the COVID-19 pandemic has an impact on daily life, such as changes in routine, activities outside the home, decreased productivity, and a reduction in the labour. This impacts psychological aspects such as feelings of anxiety, especially for final year students who are planning their future careers. This study aimed to determine the relationship between fear of COVID-19 and future career anxiety. The population in this study were final year students, which consisted of 10 male participants and 78 female participants. The research instrument used is The Fear of COVID-19 Scale (FC-19S) and the Future Career Anxiety Scale. The sampling technique used in this research is purposive sampling. The data analysis technique used was Spearman Rank correlation analysis. The analysis results stated that there was no significant relationship between the two variables, and it was very weak, with a significance value of 0.54 Keywords: Fear of COVID-19, Future career anxiety, Final year students